Analysis of Factors Affecting Clove Production in Bengkel Village, Busungbiu District, Buleleng Regency - Kadek Liana Widyaswari; Ni Luh Karmini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Clove is one of the plantation commodities that plays a significant role in the national economy, particularly as a raw material for the kretek cigarette industry, as well as the food and pharmaceutical industries. This study aims to analyze the factors influencing clove production in Bengkel Village, Busungbiu District, Buleleng Regency. The independent variables used in this study include labor, capital, harvested area, and fertilizer, while clove production serves as the dependent variable. A quantitative approach was employed using a multiple linear regression analysis in the form of a power function. Data were collected through questionnaires distributed to 140 clove farmers as respondents. The results of the study indicate that labor, capital, harvested area, and fertilizer simultaneously have a significant effect on clove production in Bengkel Village. Partially, each of these variables also has a positive and significant effect on production. These findings highlight the importance of optimizing the use of these production factors to improve clove yields in Bengkel Village, Busungbiu District, Buleleng Regency.